Local Autonomy and Democracy: Problems and Challenges in the Disruptive Era - Utama, Muhamad Adji Rahardian; Bila, Saifa (Advances in Police Science Research Journal, 2021)
Indonesia, an archipelago Republic state with numerous kind of geographic, resources, government, etc. of each region in it. In this various differentiation of each regional local government, indeed it is needed some kind of a system in which each regional local government can act in independency to control and governs each unique characteristics of its own regional local government. The Local Authonomy is a State policy through the central government is the right, authority, and obligation of the autonomous region to govern and manage its own government affairs and interests in accordance with statutory regulations it is one of the answer in which Local regional government can independency to control and governs its own characteristic resources, etc.